Enhancement of attosecond pulse in water window region by using pump-probe approach - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2018)
An effective scheme to enhance the harmonic yield and the attosecond (as) pulse signal from H-2(+) has been proposed by using the pump-probe laser field. It is found that with the help of the multi-cycle pump pulse, H-2(+) can be steered into the resonance ionization regions, where the ionization probability can be remarkably enhanced. Thus, the harmonic yield can be remarkably enhanced when a sequential mid-infrared probe pulse is added. Further, by modulating the phase of the probe pulse and by adding a controlling pulse, the harmonic cutoff can be extended up to the water window region. Finally, by the Fourier transformation of the selected harmonics on the harmonic supercontinuum, the water window attosecond pulses as short as 25 as can be obtained.
Keywords: High-order harmonic generation; single attosecond pulse; pump-probe pulse; charge resonance enhanced ionization; harmonic enhancement; ORDER HARMONIC-GENERATION; BROAD-BAND SUPERCONTINUUM; LASER-PULSE; FIELD